Cross‐sectional survey of daily junk food consumption, irregular eating, mental and physical health and parenting style of British secondary school children. Issue 4 (18th April 2013) - Zahra, J.; Ford, T.; Jodrell, D.
Abstract Background Previous research has established that poor diets and eating patterns are associated with numerous adverse health outcomes. This study explored the relationships between two specific eating behaviours (daily junk food consumption and irregular eating) and self‐reported physical and mental health of secondary school children, and their association with perceived parenting and child health. Methods 10 645 participants aged between 12 and 16 completed measures of junk food consumption, irregular eating, parental style, and mental and physical health through the use of an online survey implemented within 30 schools in a large British city. Results 2.9% of the sample reported never eating regularly and while 17.2% reported daily consumption of junk food. Young people who reported eating irregularly and consuming junk food daily were at a significantly greater risk of poorer mental (OR 5.41, 95% confidence interval 4.03–7.25 and 2.75, 95% confidence interval 1.99–3.78) and physical health (OR 4.56, 95% confidence interval 3.56–5.85 and 2.00, 95% confidence interval 1.63–2.47). Authoritative parenting was associated with healthier eating behaviours, and better mental and physical health in comparison to other parenting styles. Discussion A worrying proportion of secondary school children report unhealthy eating behaviours, particularly daily consumption of junk food, which may be associated with poorer mental and physical health. Parenting style may influence dietary habits. Interventions to improve diet may be more beneficial if also they address parenting strategies and issues related to mental and physical health.